2011
DOI: 10.1021/bi101312h
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroalcohol-Induced Modulation of the Pathway of Amyloid Protofibril Formation by Barstar

Abstract: To understand how the conformational heterogeneity of protofibrils formed by any protein, as well as the mechanisms of their formation, are modulated by a change in aggregation conditions, we studied the formation of amyloid protofibrils by barstar at low pH by multiple structural probes in the presence of hexafluoroisopropanol (HFIP). In the presence of 10% HFIP, aggregation proceeds with the transient formation of spherical oligomers and leads to the formation of both protofibrils and fibrils. Curly short pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 91 publications
1
17
0
Order By: Relevance
“…NMR studies have shown that the core of the A form is formed by the last two-thirds of the primary structure (34). The A form can be transformed into protofibrils in various aggregation conditions (21,25,32,35). Fluorescence measurements have shown that the residue-specific pattern of side-chain dynamics in the A form is similar to that in protofibrils, a result consistent with the A form being the direct precursor of the protofibrils (33).…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…NMR studies have shown that the core of the A form is formed by the last two-thirds of the primary structure (34). The A form can be transformed into protofibrils in various aggregation conditions (21,25,32,35). Fluorescence measurements have shown that the residue-specific pattern of side-chain dynamics in the A form is similar to that in protofibrils, a result consistent with the A form being the direct precursor of the protofibrils (33).…”
Section: Introductionmentioning
confidence: 66%
“…Fluorescence measurements have shown that the residue-specific pattern of side-chain dynamics in the A form is similar to that in protofibrils, a result consistent with the A form being the direct precursor of the protofibrils (33). Atomic force microscopy (AFM) (21,25,33) and transmission electron microscopy (21) studies have shown that barstar protofibrils are curvilinear fibrillar structures several hundred nanometers in length. Interestingly, protofibrils formed by barstar under different aggregation conditions differ in both external appearance and size, as well as in stability (21,25).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Similar mechanisms have been suggested for other amyloid systems, 55 including α-synuclein, 56 amyloid β, 57 islet amyloid polypeptide, 58 and several model systems. 59,60 The htt system, however, appears to be unique in that a substantial portion of the α-helix that is the basis of oligomer formation is actually retained in the final fibrils 21 (Fig. 8b).…”
Section: Discussionmentioning
confidence: 99%
“…Protein polymerization mechanisms are broadly classified under two prevalent models, namely the nucleation-elongation polymerization model and the isodesmic polymerization model [3], [4]. The latter however, is rarely encountered with few reports in protein literature till date [5], [6]. The absence of a critical concentration in isodesmic polymerization implies that aggregation can occur at nanomolar monomer concentrations which can be exploited to investigate molecular features of aggregates.…”
Section: Introductionmentioning
confidence: 99%